Increased incidence of shoulder dystocia but a declining incidence of obstetric brachial plexus palsy in vaginally delivered infants - Margareta Mollberg; Linnea V. Ladfors; Christina Strömbeck; Helen Elden; Lars Ladfors (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Obstetric brachial plexus palsy (OBPP) is a serious form of neonatal morbidity. The primary aim of this population‐based registry study was to examine temporal trends, 1997–2019, of OBPP in infants delivered vaginally in a cephalic presentation. The secondary aim was to examine temporal changes in the incidence of associated risk factors. Material and Methods This was a population‐based registry study including singleton, cephalic, vaginally delivered infants, 1997–2019, in Sweden. To compare changes in the incidence rates of OBPP and associated risk factors over time, univariate logistic regression was used and odds ratios (OR) with 95% confidence intervals (CI) were calculated. Results The incidence of OBPP in infants delivered vaginally in a cephalic presentation decreased from 3.1 per 1000 births in 1997 to 1.0 per 1000 births in 2019 (OR 0.31, 95% CI 0.24–0.40). Conversely, the incidence of shoulder dystocia increased from 2.0 per 1000 in 1997 to 3.3 per 1000 in 2019 (OR 1.64, 95% CI 1.34–2.01). Over time, the proportion of women with body mass index of 30 kg/m2 or greater increased (14.5% in 2019 compared with 8.0% in year 1997, OR 1.96, 95% CI 1.89–2.03), more women had induction of labor (20.5% in 2019 compared with 8.6% in 1997, OR 2.74, 95% CI 2.66–2.83) and epidural analgesia (41.2% in 2019 compared with 29.0% in 1997, OR 1.72, 95% CI 1.68–1.75). In contrast, there was a decrease in the rate of operative vaginal delivery (6.0% in 2019, compared with 8.1% in 1997, OR 0.72, 95% CI 0.69, 0.75) and in the proportion of infants with a birthweight greater than 4500 g (2.7% in 2019 compared with 3.8% in 1997, OR 0.70, 95% CI 0.66–0.74). The decline in the incidence of these two risk factors explained only a small fraction of the overall decrease in OBPP between 1997–2002 and 2015–219. Conclusions The incidence of OBPP in vaginally delivered infants in a cephalic presentation at birth decreased during the period 1997–2019 despite an increase in important risk factors including shoulder dystocia.